Intertextuality and the Contemporary African Novel (Nordic Journal of African Studies, 2003)
Many critical theories have evolved as a result of the pluralistic nature of the contemporary world. There is a diversion away from the monolithic theories to more synchronic ones. One of such theories that have been at the heart of this strain is intertextuality. The relevance of Intertextuality to the analysis of contemporary African Drama has been widely discussed. However, there is a dearth of studies on the place of the theory in the production and criticism of contemporary African fiction. This paper seeks to partake in the filling of this critical gap. Therefore, in the paper, an attempt is made to do a critical examination of the relevance of intertextuality to the evaluation of the contemporary African novel. It is discovered that intertextuality appears relevant to the production and criticism of the contemporary African novel. However, we hasten to declare, from the outset, that a single paper would be inadequate to explicate the practice of intertextuality in African prose fiction; we therefore limit ourselves to a representative sample of related contemporary African prose texts.